Use of the emergency department by Polish migrant workers. Issue 12 (27th November 2006) - Leaman, A M; Rysdale, E; Webber, R
Abstract : Following the accession of Poland to the European Union in 2004, large numbers of Polish migrant workers have come to the UK. We describe how this migration has impacted on an emergency department in the West Midlands, and suggest advice that should be given to such visitors about how to use the NHS.